Revision of the endemic Hawaiian sap beetle genus Apetasimus Sharp 1908 (Coleoptera: Nitidulidae) - Ewing, Curtis (Zootaxa, 2006)
The endemic Hawaiian nitidulid genus Apetasimus is revised and a key to species provided. Originally described for a single species, Apetasimus involucer, five new species are described and five species are moved from the endemic Hawaiian genus Orthostolus. The following new species are described: Apetasimus conditus sp. nov., A. ganeademus sp. nov., A. abstrusus sp. nov., A. pleomelarrosus sp. nov., and A. debbiae sp. nov. Six species previously assigned to Orthostolus and the monotypic Cyrtostolus are moved to Apetasimus; Apetasimus guttatus comb. nov., Apetasimus sordidus comb. nov., Apetasimus expers comb. nov., Apetasimus atratus comb. nov., Apetasimus kauaiensis comb. nov., and Apetasimus subalatus comb. nov. Apetasimus are arranged in three species groups: pleomelarrosus-group, involucer-group, and guttatus-group. The involucer-group is characterized by brachyptery, and are rarely collected. The pleomelarrosus-group is fully winged and one species, A. pleomelarrosus, is locally abundant on Kauai. One member of the guttatus-group, A. subalatus, is brachypterous. All guttatus-group species are presumed extinct, with the last known collection in 1935.